Pagar Air تعليم القواعد العربية باقتباس الأمثلة من الآيات القرأنية لترقية قدرة الطلاب على القواعد بمعهد علوم القرآن (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
Ulumul quran is one of islamic boarding school in banda aceh which not only focus on tahfiz alquran but also focus in studying arabic language. Nahwu is very important in maintaining fluency and language truth. Based on the observation of researchers, students in this islamic boarding school are still many who do not understand the rules of Arabic while they are able to memorize the alquran. Researchers assume that this is due to inadequate training and teachers do not accustom the use of Qur'anic verses as an example in understanding Arabic language. To overcome this problem, researchers are interested to conduct research in the form of application of examples of Qur'anic verses in studying the rules of arabic language. Researcher choose title qawaid alarabiyah biqtibas alamtsilah minal aayatil quraniyah litarqiyati qudrati atthalabah 'alal qawaid dirasah tajribiyah bima'had ulumul quran pagar air. The aim of this study is to determine the effectiveness and response of students to the use of Qur'anic verses in learning Arabic language rules. This research was an experimental research with post test only control group design. The population in this study were all students of aliyah level in ulumul quran islamic boarding school while the sample in this study were all students of class 2a and 2c. The instrument used to collect data that is post test and observation directly. The test used in this study is t test. The result of the study was the learning of Arabic rules by using Qur'anic verses could improve student’s ability in understanding Arabic rules. This can be seen from t count higher than t table or t = 1.93> from t table = 1.68, while student response in ulumul quran islamic boarding school also showed positive response seen in observation list of good value. Therefore, the research is very useful because it can increase the motivation and facilitate students in learning Arabic language and make it easier for students memorizing the Qur'anic verses in Ulumul quran islamic boarding school.
Keywords: Grammar; Example Of Quranic Verses; Student’s Skill